Resonating Culture and Religion: A Comprehensive Examination of The Tingkeban Ceremony in Nganjuk - Muh Barid Nizarudin Wajdi; Wasehudin Wasehudin; Yuli Marliana (IAIN Ponorogo, 2024)
The Tingkeban ceremony, as a cultural heritage of the Javanese community in Nganjuk, East Java, Indonesia, is faced with preservation challenges due to the influence of modernization and globalization. This research explores integrating local wisdom and Islamic values in maintaining and enriching the Tingkeban Ceremony. This study used a case study approach involving observation, interviews, and document analysis as data collection methods. This research reveals that the fusion of local wisdom and Islamic values in the Tingkeban Ceremony results in a harmonious and meaningful cultural tradition, reflecting their Javanese identity and Islamic faith. The local wisdom in the ceremony includes values such as cooperation, togetherness, and tolerance, while the integrated Islamic values include good manners, submission to Allah Swt. and cleanliness. Collaboration between various parties, including the community, religious leaders, and local government, is essential in ensuring the continuity of the Tingkeban Ceremony. Although the practice has evolved, the core values of the ceremony have been maintained and even strengthened. This study recommends efforts to increase the role and involvement of the community in preserving the Tingkeban Ceremony, develop educational programs that strengthen understanding of cultural values and Islamic faith, and promote this ceremony as an attractive cultural tourism destination in Nganjuk.